Microstructural and dielectric properties of Mo-doped barium strontium titanate nanopowders - Kelele, Kiflom Gebremedhn; Murthy, H. C. Ananda; Balachandran, Ruthramurthy; Tadesse, Aschalew; Tan, K. B. (Taylor and Francis, 2022)
The goal of this research was to examine how the dielectric properties of barium strontium titanate (BST) differ from those of BST that has been doped with molybdenum. The slow injection sol-gel technique was used. The addition of Mo6+ ions into the lattice of BST caused reduction of the mean crystallite sizes of BST, from 19.35 nm to 17.84 nm. Similarly, the mean particle size decreased from 26.02 nm all the way to 18.58 nm following the addition of Mo within the BST structure. Ultimately, the dielectric constant of BST was elevated with a maximum value of 946.3 at 1 MHz as compared to the value of 233.8 for BST. After Mo was added to BST, a reduction in dielectric loss (0.15576 to 0.0356) was also attained. Because of this, the Mo dopant in BST has significantly altered its microstructural and dielectric properties, making it suitable for multiple applications.